Hepatic schistosomiasis, upper gastrointestinal bleeding, and health related quality of life measurements from the Albert Nile Basin - Opio, Christopher K.; Kazibwe, Francis; Rejani, Lalitha; Kabatereine, Narcis B.; Ocama, Ponsiano (Journal of patient-reported outcomes, 2021)
Health related quality of life measurements are vital elements of public health surveillance that uncover unmet health needs and predict the success of health interventions. We described health related quality of life measurements using the EuroQoL 5-dimension (EQ-VAS/EQ-5D) instrument and associated factors among patients with upper gastrointestinal bleeding (UGIB) and hepatic schistosomiasis at a rural health facility in the Albert Nile Basin, Uganda. Methods and materials: This was a cross-sectional study at Pakwach Health Centre IV. Participants included adult inpatients and outpatients with a history of UGIB and ultrasound evidence of hepatic schistosomiasis. We evaluated and recorded each participant’s medical history, physical examination, laboratory tests results, ultrasound results, and endoscopy findings. We also recorded health related quality of life measurements using the EuroQoL 5-dimension instrument and derived disability weights from EQ-VAS and EQ-5D measurements. These were our dependent variables. Descriptive and inferential statistics were generated summarizing our findings. Results: We found 103 participants had a history of upper gastrointestinal bleeding and hepatosplenic schistosomiasis. Sixty percent were between the ages of 30–49 years, 59% were females, 74% were farmers, 92% had splenomegaly, 88% had varices at endoscopy, 22% were medical emergencies with acute variceal upper gastrointestinal bleeding, and 62% had anemia. Measures of the different dimensions of health from 101 participants with patient reported outcomes revealed 77 (76%) participants experienced problems in self-care, 89 (88%) participants reported anxiety or depression, and 89 (88%) participants experienced pain or discomfort. The median EQ-VAS derived disability weights and median EQ-5D index-derived disability weights were 0.3 and 0.34, respectively. Acute upper gastrointestinal bleeding, praziquantel drug treatment, and age by decade predicted higher EQ-VAS derived disability weights (p value < 0.05). Under weight (Body mass index ≤ 18.5), acute upper gastrointestinal bleeding, ascites, age by decade, female gender, and praziquantel drug treatment predicted higher EQ-5D index- derived disability weights (p value < 0.05). Conclusion: Adult patients with upper gastrointestinal bleeding and hepatic schistosomiasis from this primary health facility experience poor health and considerable health loss. Several factors predicted increased health loss. These factors probably represent key areas of health intervention towards mitigating increased health loss in this population.
Keywords: Health related quality of life measurements; Disability weights; Upper gastrointestinal bleeding; Schistosomiasis; EQ-5D/EQ-VAS